IMPLEMENTATION OF AUTHENTICITY AND NOMINAL MONEY DETECTION SYSTEMS FOR MICROCONTROLLER-BASED BLINDNESS - nfn Aprizal (Journal of Information Technology and Its Utilization, 2018)
Money is a tool used to using in sale and purchase transactions. It's has been using by peopleeverywhere. Money is a staple for everyone, even for disabilities such us blind people. The limitation of the blind people in terms of seeing is a problem in communication so they rely solely on the sense of touching and listening. This limitation can make them confuse to identified money, miscalculation, or even deceived when selling. Referring to the above, it is necessary a tool that can facilitate the blind to identify the authenticity and nominal value of money. The purpose of this study is to design a tool that can be used to detect the authenticity and nominal value of banknotes. This tool uses TCS3200-DB color sensor to detect the color of banknotes, and ultraviolet sensors to detect the authenticity of money. Then by the microcontroller converted into RGB data and issued in the form of sound. Type of research used is the type of qualitative research with experimental methods, and using Black Box testing techniques. The result of this study is the system can recognize the authenticity and nominal money. So that makes it easier for users, especially blind people in buying and selling transactions in order not to change money.